1983
DOI: 10.1136/adc.58.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic-uraemic syndrome: an analysis of prognostic features.

Abstract: SUMMARY Seventy-two children with the haemolytic-uraemic syndrome were seen between 1969 and 1980 at The Hospital for Sick Children and Guy's Hospital, London. They probably constitute the majority of such cases in south-east England during that period. Boys and girls were affected equally, the mean age at presentation was 3* 5 years, and a peak incidence of the disorder in summer months was observed. In 52 (72 %) there was a history of diarrhoea at onset. Fifty-seven (78 %) were managed by dialysis. Fifty (70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
3
3

Year Published

1987
1987
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(73 citation statements)
references
References 13 publications
4
59
3
3
Order By: Relevance
“…In the present study, the maximum number of cases of ARF was reported between the ages of 1 to 4 years. This is correlated with the studies conducted by Corlos et al and Trornpeter et al 1,2 This is because of the increased incidence of acute glomerulonephritis in this age group. This acute glomerulonephritis is usually secondary to skin infection occurring in these children.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In the present study, the maximum number of cases of ARF was reported between the ages of 1 to 4 years. This is correlated with the studies conducted by Corlos et al and Trornpeter et al 1,2 This is because of the increased incidence of acute glomerulonephritis in this age group. This acute glomerulonephritis is usually secondary to skin infection occurring in these children.…”
Section: Discussionsupporting
confidence: 78%
“…But in our study a mortality of less than 10% was noted. 2 The patient survival is very poor when the child is less than l year of age. This fact is well appreciated in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The haemolytic-uraemic syndrome (HUS) is the most common cause of acute renal failure in children and is also characterized by thrombocytopaenia, and microangiopathic haemolytic anaemia [1]. More than 80 % of HUS cases occur as a complication of intestinal infections with shiga-toxin (ST)-producing Escherichia coli (STEC) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%